Strength evaluation of earthquake-damaged reinforced concrete structure and rehabilitation strategy through the use of 3d detailed modelling - Molefe, Keaobaka (My University, 2024)
Strength evaluation of earthquake-damaged reinforced concrete structure and rehabilitation strategy through the use of 3D detailed modelling.
Keywords: Seismic Assessment of Structures; Reinforced Concrete; Nonlinear Analysis; 3D Detailed Modeling